Abnormal osteocalcin binding in rheumatoid arthritis. Issue 4 (April 1990) - Fairney, A; Patel, K V; Hollings, N P; Seifert, M H
Abstract : Studies of osteocalcin in the serum and synovial fluid of patients with rheumatoid arthritis (RA) and osteoarthritis (OA) showed the presence of significant amounts of osteocalcin in synovial fluid and that the values in RA synovial fluid were significantly lower than in OA synovial fluid. In addition, the osteocalcin in OA synovial fluid bound almost completely to hydroxyapatite, whereas a significant proportion of the osteocalcin in RA synovial fluid did not. These studies suggest that patients with severe RA produce low amounts of active osteocalcin and higher than expected amounts of inactive osteocalcin in the synovial fluid. They provide some evidence that osteoblast function may be abnormal in the osteoporosis of RA.